Interpretasi Data Geomagnet Untuk Menentukan Keberadaan Pipa Air Bawah Permukaan Bumi (Studi Kasus: Lingkungan Masjid Al-Musannif Kampus IV UINSU): (Studi Kasus: Lingkungan Masjid Al-Musannif Kampus IV UINSU) - Meilita Rahma; Ratni Sirait; Lailatul Husna Lubis (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
The existence of subsurface water pipes in the Al-Musannif Mosque environment, Campus IV UINSU, must be established. This is because it is one of the important roles of knowing the location of the pipes in order to reduce engineering accidents and as the accuracy of engineering surveys. This research was conducted using the geomagnetic method, which aims to determine the location of subsurface water pipes and to find out how the subsurface structure in the region is constructed. From this measurement, 43 points were obtained with a distance of 5 to 10 meters and with coordinates from latitude 3°49'56.24